Educação física no ensino fundamental II: um estudo sobre análise dos conteúdos de ensino em escolas públicas municipais de Castanhal-PA - SOUZA, Anne Caroline Nunes de (2019)
The present work has as object of study the systematization of the contents of Physical Education in elementary schools in the municipality of castanhal. Starting from the problematic: How does the pedagogical organization to manage the contents of the teaching of Physical Education in the fundamental area II in the municipal public schools of castanhal? For this research, a semi-structured interview was conducted with five Physical Education teachers in five elementary schools II in of castanhal. For the data analysis, the content analysis technique of Bardin (1977) was used. It was verified that the interviewed teachers systematize the contents in a random way, as they wish, and that only two teachers say they use all the content of the course in the classroom, while one minister, three content and two teachers, only teach the content of sports. In this sense, it was possible to make a diagnosis of the systematization of contents in schools and to find some existing gaps that need to be rethought.